"Science was digging its own grave": the Women's International League for Peace and Freedom and the campaign against chemical and biological warfare. Issue 4 (1st September 2020) - Balmer, Brian
Abstract : The Women's International League for Peace and Freedom (WILPF) is the oldest active women's peace organization in the world. Although their overall aim is the abolition of all war, from the outset they voiced particular opposition to chemical warfare. Later, this became a call against both chemical and biological warfare (CBW). This article draws on archival documents to trace this history, concentrating on the early days of WILPF and then on revived interest in the topic during the late 1960s and early 1970s. While early WILPF did not define CBW as an issue with any special gendered relevance for women, the historical record shows WILPF placed emphasis on its leading role in organizing opposition. It also shows a consistency of approach, WILPF often acting in an educational capacity as an informer of public opinion about the horrors of CBW. Over time, WILPF's role changed in that the leaders of the key campaigns against CBW came to regard their role as distinct from those of scientists.